Genome-Wide Analysis of DEAD-box RNA Helicase Family in Wheat (Triticum aestivum) and Functional Identification of TaDEAD-box57 in Abiotic Stress Responses - Ru, Jing-Na; Hou, Ze-Hao; Zheng, Lei; Zhao, Qi; Wang, Feng-Zhi; Chen, Jun; Zhou, Yong-Bin; Chen, Ming; Ma, You-Zhi; Xi, Ya-Jun; Xu, Zhao-Shi (Frontiers in Plant Science, 2021)
DEAD-box RNA helicases constitute the largest subfamily of RNA helicase superfamily 2 (SF2), and play crucial roles in plant growth, development, and abiotic stress responses. Wheat is one of the most important cereal crops in worldwide, and abiotic stresses greatly restrict its production. So far, the DEAD-box RNA helicase family has yet to be characterized in wheat. Here, we performed a comprehensive genome-wide analysis of the DEAD-box RNA helicase family in wheat, including phylogenetic relationships, chromosomal distribution, duplication events, and protein motifs. A total of 141 TaDEAD-box genes were identified and found to be unevenly distributed across all 21 chromosomes. Whole genome/segmental duplication was identified as the likely main driving factor for expansion of the TaDEAD-box family. Expression patterns of the 141 TaDEAD-box genes were compared across different tissues and under abiotic stresses to identify genes likely to be important in growth or stress responses. TaDEAD-box57-3B was significantly up-regulated under multiple abiotic stresses, and was therefore selected for further analysis. TaDEAD-box57-3B was localized to the cytoplasm and plasma membrane. Overexpression of TaDEAD-box57-3B in Arabidopsis thaliana improved tolerance to drought and salt stress as measured by germination rates, root lengths, fresh weights, and survival rates. Transgenic lines also showed higher levels of proline and chlorophyll and lower levels of malonaldehyde (MDA) than WT plants in response to drought or salt stress. In response to cold stress, the transgenic lines showed significantly better growth and higher survival rates than WT plants. These results indicate that TaDEAD-box57-3B may increase tolerance to drought, salt, and cold stress in transgenic plants through regulating the degree of membrane lipid peroxidation. This study provides new insights for understanding evolution and function in the TaDEAD-box gene family.